Exploring Individual Components of Sport Persistence in the Light of Gender, Education, and Level and Type of Sport - Benedek Tibor Tóth; Hanna Léna Tóth; Csanád Lukácsi; Oszkár Csaba Kocsner; Buda Lovas; Bence Tamás Selejó Joó; Hanna Czipa; Regina Bódi; Zsuzsa Lupócz; Rozália Paronai; Mátyás Kovács; Karolina Eszter Kovács (Journal of Functional Morphology and Kinesiology)
Background/Objectives: Sport persistence can be coded as an indicator of sport performance and commitment, incorporating personality traits such as resilience, adaptive coping, and positive personality traits. Thus, athletes do not merely persist in sporting activities but are qualitatively committed to them. Methods: In the present research, we used a qualitative methodology to investigate the factors underlying sport persistence, using Bronfenbrenner’s socio-ecological model. In total, 133 high school and college student-athletes were surveyed in a semi-structured interview study. We set the following research question: How do the factors involved in developing sport persistence vary across athletes’ gender, level of study, and level and type of sport? Data were analyzed along the lines of grounded theory. ATLAS.ti and IBM SPSS 22.0 statistical software were used for the analysis. Results: Our analysis divided individual motivation into intrinsic (health promotion, habituation, becoming a competitive athlete, self-improvement, self-actualization, relaxation, and sport enjoyment) and extrinsic motivation (family-related motivation, coach, social relationships, competition, livelihood, recognition). The cross-tabulation analysis revealed that contrary to the general trend, no significant differences can be experienced in the core motivational patterns contributing to sport persistence. However, significant differences could be detected concerning the level of education, level of sporting activity, and type of sport. Conclusions: Our findings not only shed light on the unique factors underlying sport persistence, but also challenge the trends observed in traditional sport motivation analyses. This insight could potentially revolutionize how we approach youth sport promotion and physical activity among young people, making our research highly relevant and impactful.